Studies on Philippine Liliaceae, Two Species from the Cordillera - Longid, Cecilie (Science Diliman: A Journal of Pure and Applied Sciences; Vol 5 No 1 (1993), 2007)
The present paper is part of a series of studies on the taxonomy of Philippine Liliaceae. Two species of Liliaceae found in the mountains of the Cordillera particularly on the slopes of Mountain Province and Ifugao; the Lilium philippinense Baker and the Dianella ensifolia Linn. are presented.
Keywords: Dianella, Liliaceae, Lilium, < I> Topotype< /I&gt